2018
DOI: 10.7287/peerj.preprints.27120v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circadian disruption and divergent microbiota acquisition under extended photoperiod regimens in chicken

Abstract: The gut microbiota is crucial for metabolic homeostasis, immunity, growth and overall health, and it recognized that early-life microbiota acquisition is a pivotal event for later life health. Recent studies show that gut microbiota diversity and functional activity are synchronized with the host circadian rhythms in healthy individuals, and circadian disruption elicits dysbiosis in mammalian models. However, no studies have determined the associations between circadian disruption in early life, microbiota col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…The majority of our MAGs belonged to the orders Oscillospirales and Lachnospirales, members of the Clostridia class. The high abundance of Clostridia observed during our study correlates with several previous studies examining the chicken caecal microbiota [20,[62][63][64][65][66][67]. This is likely the product of chicks being raised in an environment where they are not exposed to a maternal microbiota as feral hens and chicks exposed to an adult hen have microbiotas which are far less dominated by Firmicutes and contain higher abundances of Bacteroidetes [68,69].…”
Section: Discussionsupporting
confidence: 84%
“…The majority of our MAGs belonged to the orders Oscillospirales and Lachnospirales, members of the Clostridia class. The high abundance of Clostridia observed during our study correlates with several previous studies examining the chicken caecal microbiota [20,[62][63][64][65][66][67]. This is likely the product of chicks being raised in an environment where they are not exposed to a maternal microbiota as feral hens and chicks exposed to an adult hen have microbiotas which are far less dominated by Firmicutes and contain higher abundances of Bacteroidetes [68,69].…”
Section: Discussionsupporting
confidence: 84%
“…The majority of our MAGs belonged to the orders Oscillospirales and Lachnospirales , members of the Clostridia class. The high abundance of Clostridia observed during our study correlates with several previous studies examining the chicken cecal microbiota (19, 7883). This is likely the product of chicks being raised in an environment where they are not exposed to a maternal microbiota as feral hens and chicks exposed to an adult hen have microbiotas which are far less dominated by Firmicutes and contain higher abundances of Bacteroidetes (84, 85).…”
Section: Discussionsupporting
confidence: 90%
“…Distinct light–dark cycles ( L : D ) enable the development of a circadian rhythm [ 97 ]. Broilers given continuous or near-continuous light develop no circadian rhythm, whereas they do under extended dark periods such as 12 L :12 D [ 98 ] or 16 L :8 D [ 99 ]. The development of a circadian rhythm is considered an important indicator of welfare in domestic animals [ 97 ], and its disruption is associated with a variety of metabolic and immune disorders [ 98 ].…”
Section: Impact Of Light Regime On the Immune System In Chickensmentioning
confidence: 99%
“…Recently, it has also been demonstrated that the photoperiod affects cecal microbiota in chickens [ 98 ] and that gut microbiota influences behavior, physiology and immune system in chickens [ 173 , 174 ].…”
Section: Impact Of Light Regime On the Immune System In Chickensmentioning
confidence: 99%
See 1 more Smart Citation